1998
DOI: 10.1046/j.1471-4159.1998.71031034.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury‐Related Factors and Conditions Down‐Regulate the Thrombin Receptor (PAR‐1) in a Human Neuronal Cell Line

Abstract: Jou,uif ot NCUrO('/U'iniStJ'rAbstract: Previous studies have demonstrated that thrombin can induce potent effects on neural cell morphology, biochemistry, and viability. Nearly all of these effects are mediated by proteolytic activation of the thrombin receptor (PAR-i). Mechanisms of PAR-i regulation in several nonneural cell types have been shown to be novel and cell type specific; however, little is known about PAR-i regulation in neural cells. In the present study, PAR-i cell surface expression and regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 87 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…In our previous study, low concentrations of thrombin may also cause cell death after stroke. For example, a small dose of exogenous thrombin exacerbates ischemic brain injury 3, 23, 24 . It has been shown that systemic thrombin inhibition attenuated neurodegeneration and brain edema formation after transient cerebral ischemia 25, 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, low concentrations of thrombin may also cause cell death after stroke. For example, a small dose of exogenous thrombin exacerbates ischemic brain injury 3, 23, 24 . It has been shown that systemic thrombin inhibition attenuated neurodegeneration and brain edema formation after transient cerebral ischemia 25, 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al. examining Ad12 HER 10 cells, found that thrombin concentrations as low as 1.2 × 10 −3 U/mL caused cell death in hypoglycemic (0.1 m m glucose) but not in normoglycemic conditions (Weinstein et al . 1998).…”
Section: Thrombin‐induced Brain Injurymentioning
confidence: 99%
“…We transfected a plasmid expressing a bicistronic mRNA encoding dominant negative CKB and an enhanced green fluorescent protein reporter gene (EGFP) into human neuronal retinoblast cells (Ad12HER10) and observed the effect on PAR-1 signaling. The response to thrombin in these human neuronal cells has been extensively characterized and was especially suited for transfecting human CKB constructs (39,40). Most cells expressing EGFP vector alone displayed round refractile cell bodies (Fig.…”
Section: Dominant Negative Ckb Blocks Shape Changes In Retinoblastsmentioning
confidence: 99%